AT 2017gbl: a dust obscured TDE candidate in a luminous infrared galaxy. Issue 2 (19th August 2020) - Kool, E C; Reynolds, T M; Mattila, S; Kankare, E; Pérez-Torres, M A; Efstathiou, A; Ryder, S; Romero-Cañizales, C; Lu, W; Heikkilä, T; Anderson, G E; Berton, M; et al.
ABSTRACT: We present the discovery with Keck of the extremely infrared (IR) luminous transient AT 2017gbl, coincident with the Northern nucleus of the luminous infrared galaxy (LIRG) IRAS 23436+5257. Our extensive multiwavelength follow-up spans ∼900 d, including photometry and spectroscopy in the optical and IR, and (very long baseline interferometry) radio and X-ray observations. Radiative transfer modelling of the host galaxy spectral energy distribution and long-term pre-outburst variability in the mid-IR indicate the presence of a hitherto undetected dust obscured active galactic nucleus (AGN). The optical and near-IR spectra show broad ∼2000 km s −1 hydrogen, He i, and O i emission features that decrease in flux over time. Radio imaging shows a fast evolving compact source of synchrotron emission spatially coincident with AT 2017gbl. We infer a lower limit for the radiated energy of 7.3 × 10 50 erg from the IR photometry. An extremely energetic supernova would satisfy this budget, but is ruled out by the radio counterpart evolution. Instead, we propose AT 2017gbl is related to an accretion event by the central supermassive black hole, where the spectral signatures originate in the AGN broad line region and the IR photometry is consistent with re-radiation by polar dust. Given the fast evolution of AT 2017gbl, we deem a tidal disruption event (TDE) of a star a more plausible scenario than a dramatic change in the AGN accretion rate. This makes AT 2017gbl the third TDE candidate to be hosted by a LIRG, in contrast to the so far considered TDE population discovered at optical wavelengths and hosted preferably by post-starburst galaxies.